A Theory of Poverty: Legal Immobility - Sara S. Greene (Washington University Law Review, 2019)
The puzzle of why the cycle of poverty persists and upward socioeconomic mobility is so difficult has long captivated scholars and the public alike. Yet with all of the attention that has been paid to poverty, the crucial role of the law, particularly state and local law, in perpetuating poverty is largely ignored. This Article offers a new theory of poverty, one that introduces the concept of legal immobility. Legal immobility considers the cumulative effects of state and local laws as a mechanism through which poverty is perpetuated and upward socioeconomic mobility is stunted. The Article provides an initial description and normative account of this under-theorized aspect of our laws and argues that in order to fully understand poverty, a more complete understanding of the relationship between law and poverty is needed. After discussing several examples of laws that can contribute to legal immobility (everything from state and local tax laws to occupational licensing laws), the Article offers a three-prong theory to help understand the distinct pathways through which individual laws that contribute to legal immobility function: (1) calculated exploitation; (2) gratuitous management; and (3) routine neglect. This framework provides a guide for future work to build on legal immobility theory. By bringing to light the cumulative effects of local and state laws in perpetuating poverty, the goal is for legal immobility theory to ultimately help lawmakers develop new structural approaches to tackling poverty.
Keywords: Legal immobility; Poverty law; Calculated exploitation; Gratuitous management; Routine neglect; Poverty policy; Social policy; Socioeconomic status; Class mobility; Socioeconomic mobility